Deciphering Human Cell-Autonomous Anti-HSV-1 Immunity in the Central Nervous System - Lafaille, Fabien G.; Ciancanelli, Michael J.; Studer, Lorenz; Smith, Gregory; Notarangelo, Luigi; Casanova, Jean-Laurent; Zhang, Shen-Ying (Frontiers in Immunology, 2015)
Herpes simplex virus 1 (HSV-1) is a common virus that can rarely invade the human central nervous system (CNS), causing devastating encephalitis. The permissiveness to HSV-1 of the various relevant cell types of the CNS, neurons, astrocytes, oligodendrocytes, and microglia cells, as well as their response to viral infection, has been extensively studied in humans and other animals. Nevertheless, human CNS cell-based models of anti-HSV-1 immunity are of particular importance, as responses to any given neurotropic virus may differ between humans and other animals. Human CNS neuron cell lines as well as primary human CNS neurons, astrocytes, and microglia cells cultured/isolated from embryos or cadavers, have enabled the study of cell-autonomous anti-HSV-1 immunity in vitro. However, the paucity of biological samples and their lack of purity have hindered progress in the field, which furthermore suffers from the absence of testable primary human oligodendrocytes. Recently, the authors have established a human induced pluripotent stem cells (hiPSCs)-based model of anti-HSV-1 immunity in neurons, oligodendrocyte precursor cells, astrocytes, and neural stem cells, which has widened the scope of possible in vitro studies while permitting in-depth explorations. This mini-review summarizes the available data on human primary and iPSC-derived CNS cells for anti-HSV-1 immunity. The hiPSC-mediated study of anti-viral immunity in both healthy individuals and patients with viral encephalitis will be a powerful tool in dissecting the disease pathogenesis of CNS infections with HSV-1 and other neurotropic viruses.